Allegorical engraving of the peace between France and Savoy (Almanach... - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Allegorical engraving of the peace between France and Savoy (Almanach royal, 1714). Louis XIV. 1714 peace between France and Savoy
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons